Aquatic dance flies of Czech Republic (Empididae: Clinocerinae and Hemerodromiinae): new records and updated species list - Ivković, Marija; Čorkalo, Marko; Tkoč, Michal (Zootaxa, 2020)
New records are provided for aquatic dance flies from Czech Republic, with new distribution records for 19 species in six different genera. Four species are newly recorded from Czech Republic: Dolichocephala ocellata (Costa, 1854), Kowarzia tenella (Wahlberg, 1844), Wiedemannia insularis Collin, 1927 and Wiedemannia wachtli (Mik, 1880). There are now 43 species of aquatic dance flies recorded from Czech Republic.